ANALISIS FAKTOR-FAKTOR KUNCI DARI NIAT PEMBELIAN KEMBALI SECARA ONLINE (STUDY KASUS PADA KONSUMEN FESH SHOP) - Trisnawati Ella; Suroso AguS; Kumorohadi Untrung (Jurnal Bisnis dan Ekonomi, 2012)
The purpose of this study is to analyze the key factors to identify the intention of individuals to repurchasing at online shop.Respondents are consumers of fesh Shop. 136 respondents completed questionnaires were given. Data analysis usingStructural Equation Model (SEM) to determine the relationship between variables. The results of this research are that theperception ease of use, confirmation, thrust, perceptions of usefulness, satisfaction, perceived enjoyment, and privacy has apositive influence on repurchase intention on selling online.Key words: perceived ease of use, confirmation, trust, perceived usefulness, satisfaction, perceived enjoyment, privacy,repurchase intention, online shop.